Factors associated with traffic crashes on urban freeways - Aschalew Kassu (Transportation Engineering, 2020)
The majority of earlier works suggested that traffic fatalities in a rural section of highways are relatively higher than those observed in urban areas. However, the recent report released by the National Highway Traffic Safety Administration (NHTSA) described the trend that the urban area highway fatalities in the last four years are higher than the crashes that occurred on a rural section of the highway segments. In the present work, the key factors influencing fatal, non-fatal injury and property damage only crash on four and six-lane urban interstate highway segments are analyzed. A negative binomial regression approach was used for the analyses of the three crash categories, and a meaningful statistical interpretation of the developed model estimates are provided in terms of the incident rate ratio. The results of the study suggest that traffic volume, median type, and the number of lanes were factors associated with fatal, non-fatal injury, and property damage only crashes. All the categories of the horizontal and vertical geometries of the roadway segment were found to be critical factors influencing property damage only crashes. The results also showed that the effect of drivers’ gender was insignificant across the three crash categories.